PENGARUH PENGARUH MODEL PROBLEM BASED LEARNING BERBANTU MEDIA BAAMBOOZLE TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Aulia, Asti; Hadnistia Darmawan, Nurani; Ngaini, Rahma Nur; Ghina Suryawirawati, Ismi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Critical thinking is one of the essential twenty-first century competencies that should be developed through mathematics learning in elementary schools. However, mathematics instruction is still predominantly teacher-centered, limiting students' opportunities to analyze and solve problems critically. This study aimed to examine the effect of the Problem-Based Learning (PBL) model assisted by baamboozle media on the critical thinking skills of fourth-grade students at SDN Sukamukti in learning fractions. This study employed a quantitative approach using a pre-experimental method with a one-group pretest-posttest design. The participants consisted of 30 fourth-grade students selected through saturated sampling. Data were collected using a critical thinking test and an observation sheet to assess the implementation of the learning process. Data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, the paired sample t-test, and the N-Gain test. The findings revealed that the mean score of students' critical thinking skills increased from 51.47 in the pretest to 74.27 in the posttest. The paired sample t-test indicated a significance value of 0.001 (p < 0.05), while the average N-Gain score was 0.5056, categorized as moderate. In addition, the implementation of learning reached 94%, indicating a very good level of implementation. These findings demonstrate that the Problem-Based Learning model assisted by Baamboozle media has a significant positive effect and can serve as an effective alternative for improving elementary school students' critical thinking skills in mathematics learning.